Antibacterial Efficacy of Exogenous Nitric Oxide on Periodontal Pathogens. (November 2014) - Backlund, C.J.; Sergesketter, A.R.; Offenbacher, S.; Schoenfisch, M.H.
Current treatments for periodontitis ( e.g ., scaling/root planing and chlorhexidine) have limited efficacy since they fail to suppress microbial biofilms satisfactorily over time, and the use of adjunctive antimicrobials can promote the emergence of antibiotic-resistant organisms. Herein, we report the novel application of nitric oxide (NO)-releasing scaffolds ( i.e ., dendrimers and silica particles) as anti-periodontopathogenic agents. The effectiveness of macromolecular NO release was demonstrated by a 3-log reduction in periodontopathogenic Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis viability. In contrast, Streptococcus mutans and Streptococcus sanguinis, caries-associated organisms, were substantially less sensitive to NO treatment. Both dendrimer- and silica-based NO release exhibited substantially less toxicity to human gingival fibroblasts at concentrations necessary to eradicate periodontopathogens than did clinical concentrations of chlorhexidine. These results suggest the potential utility of macromolecular NO-release scaffolds as a novel platform for the development of periodontal disease therapeutics.